Hilar mossy cell circuitry controlling dentate granule cell excitability - Jinde, Seiichiro; Zsiros, Veronika; Nakazawa, Kazu (Frontiers in Neural Circuits, 2013)
Glutamatergic hilar mossy cells of the dentate gyrus can either excite or inhibit distant granule cells, depending on whether their direct excitatory projections to granule cells or their projections to local inhibitory interneurons dominate. However, it remains controversial whether the net effect of mossy cell loss is granule cell excitation or inhibition. Clarifying this controversy has particular relevance to temporal lobe epilepsy, which is marked by dentate granule cell hyperexcitability and extensive loss of dentate hilar mossy cells. Two diametrically opposed hypotheses have been advanced to explain this granule cell hyperexcitability – the “dormant basket cell” and the “irritable mossy cell” hypotheses. The “dormant basket cell” hypothesis proposes that mossy cells normally exert a net inhibitory effect on granule cells and therefore their loss causes dentate granule cell hyperexcitability. The “irritable mossy cell” hypothesis takes the opposite view that mossy cells normally excite granule cells and that the surviving mossy cells in epilepsy increase their activity, causing granule cell excitation. The inability to eliminate mossy cells selectively has made it difficult to test these two opposing hypotheses. To this end, we developed a transgenic toxin-mediated, mossy cell-ablation mouse line. Using these mutants, we demonstrated that the extensive elimination of hilar mossy cells causes granule cell hyperexcitability, although the mossy cell loss observed appeared insufficient to cause clinical epilepsy. In this review, we focus on this topic and also suggest that different interneuron populations may mediate mossy cell-induced translamellar lateral inhibition and intralamellar recurrent inhibition. These unique local circuits in the dentate hilar region may be centrally involved in the functional organization of the dentate gyrus.